MIKROBIOTA POSTMORTEM SEBAGAI PENANDA BIOLOGIS PERKIRAAN WAKTU KEMATIAN: SUATU KAJIAN LITERATUR - Insil Pendri Hariyani; Resti Rahmadika Akbar; Mutiara Anissa (Nusantara Hasana Journal, 2025)
Determining the time of death (Postmortem Interval/PMI) is a crucial aspect of forensic medical investigations. Classical methods such as measuring body temperature, rigor mortis, and livor mortis are often inaccurate in tropical environments that accelerate decomposition. Microbiology-based approaches, particularly postmortem microbiota (thanatomicrobiome) analysis, offer more objective biological indicators. Recent literature indicates a regular pattern of microbial succession in various body locations after death, including the oral cavity, stomach, and rectum. Environmental factors such as temperature and humidity significantly influence microbiota dynamics, necessitating local mapping for tropical contexts. This review discusses recent research findings on postmortem microbiota patterns, identification methods (molecular and conventional), and their potential use as a basis for more accurate PMI estimation in Indonesia.